The Moderating Effect of Guanxi on the Dynamic Capacity and Competitive Advantage of Chinese International Contractors. (1st August 2018) - Lin, Yi-Hsin; Chen, Qihui; Liao, Pin-Chao; Chen, Po-Han; Cheng, Shuping
Abstract : With the active support of the national policy "One Belt and One Road" Initiative, Chinese contractors seized this historic opportunity to accelerate strategic globalization, and they gradually stood out in international construction projects owing to their low-cost advantage. However, despite China having large-scale contractors and wide-range business, compared to developed countries, a considerably large gap still exists. China is confronted with complex and changeable international projects filled with increasing competition. Thus, it is both a focus issue and a major task for Chinese international contractors, and many scholars, to consider how Chinese contractors can obtain and maintain long-term competitive advantages to improve their capabilities in response to dynamic environmental changes. Therefore, the objectives of this study are (1) to study the influence of the dynamic capability of Chinese contractors on competitive advantage in a project and (2) to explore the moderating effect of Chinese guanxi on the dynamic capability and competitive advantage of Chinese international contractors. This study primarily aimed at researching the impact of dynamic capacity of Chinese contractors on competitive advantage and the moderating effects of Chinese guanxi. The findings suggest that the environmental perception capability and the integration and coordination capability of the dynamic capability have a significant positive effect on the project competitive advantage; business guanxi positively moderates the relationship between the environmental perception capability and the competitive advantage. Business guanxi also negatively moderates the relationship between learning ability and competitive advantage, while political guanxi negatively moderates the relationship between the environmental perception capability and competitive advantage. This paper contributes to the construction management literature not only by providing empirical evidence on the dynamic capability and competitive advantage of Chinese contractors but also by expanding guanxi research. The results may also help Chinese contractors by providing strategic reform guidance and sustainable development in international construction projects.